2017
DOI: 10.1097/md.0000000000008656
|View full text |Cite
|
Sign up to set email alerts
|

Topical steroids eye drops in conjunctival reactive lymphoid hyperplasia

Abstract: Rationale:Conjunctival lymphoproliferative lesions constitute a significant diagnostic challenge and it is essential to exclude neoplastic lesions. Histopathological and immunohistochemical tests are very useful in establishing the correct diagnosis. Reactive lymphoid hyperplasia (RLH) is part of a spectrum of lymphocytic infiltrative disorders. Evidence is scarce regarding appropriate treatment of conjunctival RLH. We report a case treated with topical corticosteroid.Patient concerns:A 40 year-old female pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Literature review revealed 235 reported cases of BRLH in 36 published studies, which are presented in Table 1 [1, 2, 412, 1438]. The mean age at diagnosis of all reported cases was 35.2 years (range, 5 to 91 years), 54% of the patients whose gender was reported were male (100/186), and 46% were female (86/186).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature review revealed 235 reported cases of BRLH in 36 published studies, which are presented in Table 1 [1, 2, 412, 1438]. The mean age at diagnosis of all reported cases was 35.2 years (range, 5 to 91 years), 54% of the patients whose gender was reported were male (100/186), and 46% were female (86/186).…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Table 1) Fifty-two of these 96 patients (54.1%) underwent excisional biopsy of the BRLH lesions; two of them had residual lesions, which were observed [5, 25], and two received a post-operative course of oral corticosteroids, which failed to eradicate the lesions [5, 19]. Nine patients (9/96 or 9.3%) were treated with topical corticosteroids; only one patient showed a complete response [14] while the rest of the patients experienced a partial response [2, 6, 15]. Two patients treated with topical antihistamines and one patient treated with a topical antibiotic ointment also had a partial response and their lesions were subsequently excised [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation